RETRACTED - Antibacterial and Antibiofilm Activity of Hypericum Perforatum L. Extract on Bacteria Isolated from Used Cosmetic Tools - Khuloud Aljabu,; Ipek Ada Alver, (AlQalam Journal of Medical and Applied Sciences, 2026)
The article ‘Antibacterial and Antibiofilm Activity of Hypericum Perforatum L. Extract on Bacteria Isolated from Used Cosmetic Tools’ by Khuloud Aljabu and Ipek Ada Alver, published in Alq J Med App Sci Vol 9(2): 403–409, DOI: 10.54361/ajmas.269214, has been retracted at the authors’ request due to that the article was submitted and published by the first author without obtaining the approval of the thesis supervisor and without sharing the final version of the manuscript with the supervisor (second author) prior to submission.